An Adaptation Study of Measurement Properties for the Characteristics of Resilience in Sports Team Inventory - Recep Gorgulu; Ender Senel; İlhan Adilogulları; Mevlut Yildiz (MDPI AG, 2018)
This multi-study paper reports the translation process and the validity and reliability analysis of the Characteristics of Resilience in Sports Teams Inventory (CREST) for the use of Turkish population. In three related studies, 414 team sports athletes from Turkey were sampled. We adopted Beaton et al.’s (2000) methodology for the translation of self-report measures for cross-cultural adaption studies. The first study provided content validity for an initial item set as the preliminary study. The second study explored the factor analysis of the CREST structure. The third study explored re-testing of the explored structure in a different set of participants and criterion-related validity provided. The analysis of Study 1 revealed that the items were understood by the participants and ready for application for the general Turkish population. The exploratory factor analysis in the Study 2 revealed that the CREST had two sub-dimensions as it was in the original inventory. The Cronbach’s alpha values for the dimensions of demonstrating resilience characteristics and vulnerabilities shown under pressure were 0.94 and 0.90, respectively. The Kaiser-Meyer-Olkin value was 0.94. The confirmatory factor analysis in the third study showed that the structure of the inventory was confirmed in another sports context. Accordingly, the CREST is a valid and reliable tool for use by Turkish athletes and to measure team resilience that is one of the critical determinants of team performance. Further understanding of team resilience as a process can be gain by using the CREST, especially in future process-oriented research for team sports.